2015
DOI: 10.14311/ap.2015.55.0229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postural Instability in Patients With a Neurological Disorder Using a Tri-Axial Accelerometer

Abstract: Abstract. Current techniques for quantifying human postural stability during quiet standing have several limitations. The main problem is that only two movement variables are evaluated, though a better description of complex three-dimensional (3-D) movements can be provided with the use of three variables. A single tri-axial accelerometer placed on the trunk was used to measure 3-D data. We are able to evaluate 3-D movements using a method based on the volume of confidence ellipsoid (VE) of the set of points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Data have even been obtained that show greater sensitivity to the accelerometers in front of the force platforms [84]. The accelerometric evaluation of the balance has been compared repeatedly with the results in clinical trials and tests, with positive results in different populations, such as elderly people with a history of falls [93,94] or a cerebrovascular accident [94], children with dyslexia [95], patients with Huntington’s [96], with Parkinson’s disease [47], with progressive cerebellar ataxia [97], and with vestibular disorders [98].…”
Section: Discussionmentioning
confidence: 99%
“…Data have even been obtained that show greater sensitivity to the accelerometers in front of the force platforms [84]. The accelerometric evaluation of the balance has been compared repeatedly with the results in clinical trials and tests, with positive results in different populations, such as elderly people with a history of falls [93,94] or a cerebrovascular accident [94], children with dyslexia [95], patients with Huntington’s [96], with Parkinson’s disease [47], with progressive cerebellar ataxia [97], and with vestibular disorders [98].…”
Section: Discussionmentioning
confidence: 99%
“…The second analysis is focused to describe the peculiar behaviour of each group in the three tasks. To explicitly analyse postural control differences between participants, we considered the three-dimensional data of COP and COM positions and compared the volumes of prediction ellipsoid [25][26][27][28][29] of each group by means of the Generalized Variance (GV), a scalar measure of dispersion defined as the determinant of the sample covariance matrix and proportional to specific equal- probability contour (i.e., standard ellipsoid) of the measured data. Between groups inferential tests were conducted on GVs with a Chi-square log-Likelihood Ratio Test [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted and this follow-up study on postural instability in patients with VS using an IMU placed on the patient's trunk and the Leibniz method show that the method presented is suitable for the identification of postural balance problems. This technique described allows for the study of three measured variables (three angles and three accelerations) of 3-D body movement [ 41 , 42 ]. Adopting this approach overcomes the greatest limitation of traditional methods relying on just two variables, each in one of the two human body axes of the transverse level (as used in CoP research) [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique described allows for the study of three measured variables (three angles and three accelerations) of 3-D body movement [ 41 , 42 ]. Adopting this approach overcomes the greatest limitation of traditional methods relying on just two variables, each in one of the two human body axes of the transverse level (as used in CoP research) [ 41 , 42 ]. Although this new technique has never been used for the study of patients with VS, its application can be found in other fields, for data analysis obtained by an IMU in cell phones or electronic watches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation